2020
DOI: 10.3390/ijerph17144981
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Competitiveness through the Implementation of Lean Management in Healthcare

Abstract: The main aim of this paper was two-fold: first, to design a participative methodology that facilitates lean management implementation in healthcare by adopting the action research approach; second, to illustrate the usefulness of this methodology by applying it to the sleep unit of a public hospital in Spain. This methodology proposes the implementation of lean management in its broadest sense: adopting both lean principles and some of its practical tools or practices in order to achieve competitive ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 63 publications
0
35
0
1
Order By: Relevance
“…Previous research similar to this paper [ 18 ] suggests that there are not many references in the health care field to the action research approach [ 49 , 50 , 51 ]; it is a sector more focused on case studies.…”
Section: Materials and Methods: Model For The Implementation Of Prmentioning
confidence: 83%
See 4 more Smart Citations
“…Previous research similar to this paper [ 18 ] suggests that there are not many references in the health care field to the action research approach [ 49 , 50 , 51 ]; it is a sector more focused on case studies.…”
Section: Materials and Methods: Model For The Implementation Of Prmentioning
confidence: 83%
“…Following the principles of the Lean philosophy [ 47 , 48 ] and using action research methodology [ 18 ], this section presents a scientific methodology as shown in Figure 1 below that allows the redesign of processes and that can be replicated with the same purpose in other health centers in order to improve patient care.…”
Section: Materials and Methods: Model For The Implementation Of Prmentioning
confidence: 99%
See 3 more Smart Citations